Athlete anxiety questionnaire: the development and validation of a new questionnaire for assessing the anxiety, concentration and self-confidence of athletes - Trpkovici, Melinda; Pálvölgyi, Ágnes; Makai, Alexandra; Prémusz, Viktória; Ács, Pongrác (Frontiers in Psychology, 2023)
Introduction: Anxiety is one of the most prevalent issues among athletes. Therefore, measuring the stress caused by high-stakes situations could be important for investigating the issue. In sports psychology literature, no valid and reliable questionnaire is available in Hungarian for assessing the anxiety experienced by athletes in high-stakes situations. This study aimed to create a new Hungarian questionnaire to measure anxiety, self-confidence, and concentration during high-stakes contests. Methods: 263 athletes of various sports participated in the cross-sectional study (age: 16.18±3.46 years). The structure of the Anxiety Athletes Questionnaire (AAQ) was examined through factor analysis, where exploratory factor analysis (EFA) as well as confirmatory factor analysis (CFA) were carried out. The internal consistency of the subscales of AAQ was measured by Cronbach's alpha. Through a convergent validity test, the AAQ questionnaire was compared to the subscales of the CSAI-2 and ACSI-28 questionnaire subscales by Spearman's rank correlation coefficients. Through a discriminant validity analysis, the differences by age group, sex, and sport variables were examined by AAQ scores. The Mann-Whitney U and Kruskal-Wallis H tests were utilized in the analysis. The SPSS 28.0 software was used for the statistical analysis, and the level of significance was set at p<0.05. Results: 4 factors have been identified through the EFA. The CFA analysis showed the fourfactor model an acceptable model fit (SRMR, RMSEA CFI, TLI). Cronbach's alpha of the four subscales showed acceptable internal consistency (cognitive anxiety: α=0.871; somatic anxiety: α=0.700; self-confidence: α=0.832; concentration: α=0.747;). The convergent validity showed a weak or moderate, significant relationship between AAQ subscales and subscales of CSAI and ACSI (R=-0.398-0.412). Conclusion: The Athlete Anxiety Questionnaire can be considered a reliable and valid This is a provisional file, not the final typeset article measurement tool for measuring athletes' anxiety, self-confidence and concentration in high-stakes situations.